ASSESSMENT OF OCCUPATIONAL HAZARD AND INJURY RISKS IN THE HOTEL INDUSTRY: FOCUSING ON FOODSERVICES PERSONNEL IN SABAH, MALAYSIA - D.K. Rafidzah, L.Y. Kwan2 & R. H. Leoneeta (International Journal of Research Science and Management, 2018)
This study aims to determine the risks for physical, chemical, biological and psychosocial hazard that are related to occupational health and safety as well as to determine the type of injury occur mostly among foodservice employee. Questionnaire was distributed to 128 foodservice workers of 4-5 stars hotels in Kota Kinabalu, Sabah. Result found that psychosocial hazard (3.29±.96) was more likely to occur whereas chemical hazard (4.13±.74) was less likely to occur. ANOVA analysis showed physical and psychosocial hazard have significant difference (p≤0.05). The post hoc test (Scheffé) shows only chemical and biological hazard have equal mean of hazard. For the type of injury, emotional stress occur the most (3.63±1.15) whereas electrocution occur the least (1.37±.64). Independent T-test indicated that burns (P≤0.05), cuts and laceration (P≤0.05) and dermatitis (P≤0.05) showed significance difference in term of occurrence frequency between kitchen and service workers. As conclusion, attention should be given to the physical and psychosocial hazards and injury associated with it as it shows a higher risk of occurrences.